Dziesięć sążni w dół albo dziesięć uwag o płynności i głębi - Krzysztof Hoffmann (Przestrzenie Teorii)
The text is an interpretation of Stanisław Barańczak’s poem From the introduction to a phrasebook. The reading of the lyric reveals a basic organizing opposition, i.e. the dichotomy of “liquidity” (“shallowness”) and “depth”. The final parts of the interpretation present the role of poetic language (defined through modernistic concepts) as a language that gives the opportunity to counter the aporia inherent in every act of communication.